Evolution of Maya polities in the ancient Mesoamerican system. - Cioffi-Revilla, Claudio; Landman, Todd (International Studies Quarterly)
The analysis of politics in antiquity presents new opportunities for political science and international relations, particularly the ancient New World (c. 2000 B.C. to A.D. 1521). Governance through leadership and institutions, collective action, war and peace, alliance dynamics, regional hegemonies, interstate rivalries, and other universal patterns of world politics existed in Mesoamerica, antedating the modern state system. We report findings from a study to record systematically the rise and fall of Maya polities in the Mesoamerican political system, using sources from archaeology and epigraphy. Based on tests of competing hypotheses and new distribution statistics and hazard rates (survival analysis) for 72 Maya polities, our findings support a model of Maya political dynamics based on Preclassic origins, punctuated phases of development, multiple cycles of system expansion and collapse, and weaker political stability for increasingly complex polities. We draw two main implications: (a) a new theory of the Maya political collapse(s), based on their failure to politically integrate; and (b) confirmation for a new periodization of Maya political evolution, different from the traditional cultural periodization, based on several cycles of rise-and-fall, not just one. Our findings may also make possible future investigations in areas such as the war-polarity and war-alliances hypotheses.